Assessment of benefits and risks associated with dengue vaccination at the individual and population levels: a dynamic modeling approach - Coudeville, Laurent; Baurin, Nicolas; Olivera-Botello, Gustavo (Expert review of vaccines, 2018)
A case-cohort study, using a novel assay and data from three dengue vaccine efficacy trials, highlighted differences in vaccination outcomes according to baseline serostatus. Based on these results, we explored, with a model, the benefits and risks associated with vaccination. Parameters of a previously developed transmission model were estimated with subject-level data from a case-cohort study. The model was used to assess vaccination outcomes for a range of transmission settings over 5-30 years, with or without indirect protection. Symptomatic dengue cases, dengue hospitalizations, and severe dengue cases. The model is consistent with previous results indicating a transitory period at increased risk for dengue-seronegative vaccine recipients (setting-dependent duration) and long-term benefits for dengue-seropositive recipients. At the population level, benefits to seropositive individuals over 10 years outweighed the risk to those seronegative in moderate to high transmission settings (≥50% seropositivity at age 9), especially in high transmission settings (no excess hospitalizations in dengue-seronegative for ≥80% seropositivity at age 9). Results were more favorable when longer time horizons or indirect protection were considered. Results indicate a public health benefit associated with dengue vaccination especially in high-transmission settings, even with the initial excess risks to dengue-seronegative patients which diminish over time.